(untitled) (Third Sector Social Economic Review, 2026)
This study examines the relationship between exports by payment method and foreign demand, the real exchange rate, and uncertainty indicators in Türkiye from 2013Q1 to 2024Q4. The analysis considers four payment methods, cash against goods, advance payment, letter of credit, and cash against documents, and uses the Global Economic Policy Uncertainty (GEPU) index and the World Uncertainty Index (WUI) to capture uncertainty. Both symmetric and asymmetric ARDL models are applied, and the robustness of results is checked with CCR, DOLS, and FMOLS estimators. Findings show that the economic growth of trading partners supports exports. Real exchange rate appreciation reduces exports for all methods except cash against documents. Symmetric results indicate a positive link between uncertainty and exports for letters of credit and advance payments, but a negative link for cash against goods; no significant effect is found for cash against documents. Asymmetric analyses have revealed the existence of asymmetric relationships between uncertainties and exports in all methods except cash against documents. In this context, to support exports during periods of uncertainty, letters of credit and advance payments should be encouraged, while risk mitigation measures should be implemented for cash against goods.